2015
DOI: 10.1016/j.jsg.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts in sillimanite deformation in felsic tectonites from anhydrous granulite- and hydrous amphibolite-facies shear zones, western Canadian Shield

Abstract: a b s t r a c tThe deformation behavior of crustal materials in variably hydrated metamorphic environments can significantly influence the rheological and seismic properties of continental crust. Optical observations and electron backscatter diffraction (EBSD) analyses are used to characterize sillimanite deformation behavior in felsic tectonites from two deformation settings in the Athabasca granulite terrane, western Canadian Shield. Under estimated conditions of 0.8e1.0 GPa, 725e850 C in the Cora Lake shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…One major characteristic of the eastern Athabasca granulite terrane is a block style architecture, with distinct lithotectonic subdomains divided by thick ductile shear zones (briefly discussed below; Flowers et al, 2006b;Leslie et al, 2015). Detailed work has demonstrated that the steeply to moderately dipping shear zones that divide subdomains are Paleoproterozoic in age (Williams et al, 2009;Mahan et al, 2006a;Dumond et al, 2013;Regan et al 2014).…”
Section: The Athabasca Granulite Terranementioning
confidence: 99%
See 3 more Smart Citations
“…One major characteristic of the eastern Athabasca granulite terrane is a block style architecture, with distinct lithotectonic subdomains divided by thick ductile shear zones (briefly discussed below; Flowers et al, 2006b;Leslie et al, 2015). Detailed work has demonstrated that the steeply to moderately dipping shear zones that divide subdomains are Paleoproterozoic in age (Williams et al, 2009;Mahan et al, 2006a;Dumond et al, 2013;Regan et al 2014).…”
Section: The Athabasca Granulite Terranementioning
confidence: 99%
“…The Upper Deck (also referred to as the southern subdomain (Baldwin et al 2004;Flowers et al, 2006b)) consists of abundant migmatitic paragneiss traditionally referred to as felsic granulite, mafic granulite, and minor eclogite (Snoeyboss et al, 1995;Baldwin et al, 2003;2004). The dominant rock type is a garnetiferous quartzofeldspathic gneiss, interpreted to represent a deformed migmatite that has had variable amounts of melt loss and is referred to as the "white gneiss" (Snoeyenboes et al, 1995;Baldwin et al, 2004;Dumond et al, 2015). The white gneiss contains an assemblage of ternary feldspar, quartz, kyanite, garnet, and rutile +/-sillimanite (Snoeyenboes et al, 1995).…”
Section: The Athabasca Granulite Terranementioning
confidence: 99%
See 2 more Smart Citations
“…Based on these results, they reveal the sensitivity of seismic anisotropy calculations of gabbroic rocks to texture symmetry, which should definitively be taken into account when interpreting geophysical data and building models of the lower crust. Leslie et al (2015) compares sillimanite microstructure and texture development in felsic tectonites from both anhydrous granulite-and hydrous amphibolite-facies shear zones (Athabasca granulite terrane, western Canadian Shield), primarily using electron backscatter diffraction. They reveal that sillimanite deformation is strongly influenced by temperature, fluid content and mineralogy of the sillimanite-bearing rock.…”
mentioning
confidence: 99%